PENERAPAN TEKNOLOGI PEMBELAJARAN AUDIO VISUAL TERHADAP HASIL BELAJAR DRIBBLING SEPAK BOLA DI SMA NEGERI 1 BONDOWOSO (STUDI PADA SISWA KELAS XII DI SMAN 1 BONDOWOSO) - SOEFYAN, ACHMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In Educational, the role of the teacher is very important, it needs a learning model which is appropriate so that the teaching learning process can run effectively and can support the improvement of students’ ability to gain the goals. One of them is by using Application of Learning Technology (Video) Against Football Dribbling Learning Outcomes. The teacher is a key to improving the quality of education. They are in central point in every educational reformation way which is directed to the quality changing. The purpose of this research is to understand the influence of audio visual media in teaching learning outcomes Physical education dribbling soccer at senior hight school 1 Bondowoso. Objectives of this research is a class XII student of senior hight school 1 Bondowoso 2011-2012 school year, amounting to 41 students. How sampling of research used in this study is one Group Pretest-Posttest Design. In this design there is no control group, and the subjects are not placed randomly. The advantages of this design are not placed randomly. This design does pretest and posttest that can be known with certainty differences in results due to the treatment given. That way students obtain class XII IPA 1 totaling 41 people, were treated by the application of audio-visual media in teaching Physical education. The results are as follows: (1) There are significant differences after the research process, the results of this study concluded that there are significant differences between learning outcomes soccer dribbling before and after learning penjasorkes (video) at senior hight school 1 Bondowoso. (2) Value Physical education learning outcomes prior learning (video) lower than on learning outcomes after learning Physical education (video). (3) The application of video on penjasorkes learning can provide a positive enhancement to the learning outcomes dribbling. Keywords:  Application of video on Physical education learning, learning outcomes soccer dribbling.